Person‐centred discharge education following coronary artery bypass graft: A critical review. Issue 23 (8th October 2017) - Rushton, Melanie; Howarth, Michelle; Grant, Maria J; Astin, Felicity
Abstract : Aims and objectives: To examine the extent that individualised education helps reduce depression and anxiety and improves self‐care for people who have undergone coronary artery bypass graft surgery. Background: Individualised discharge planning is increasingly important following cardiac surgery due to recurrent admissions as well as the issue of anxiety and depression, often due to lack of preparation. The hospital to home transition is fundamental in the recovery process. Individualised education and person‐centred care ensure that patients' educational needs are met. This empowers patients, increasing self‐efficacy or confidence, resulting in autonomy, a smoother discharge process and avoiding postdischarge problems and rehospitalisation. Design: A critical review of published peer‐reviewed literature was conducted. Methods: Electronic databases searched included MEDLINE, CINAHL, the Cochrane Library and PsychInfo 2009–2015. Results: Eight articles were identified for review, and a Critical Appraisal Skills Programme framework was used to determine the quality of the papers, all of the papers focussed on coronary artery bypass graft. The designs were typically experimental or quasi‐experimental with two reviews. Conclusion: A greater understanding of the patients' needs allows tailored education to be provided, which promotes self‐care management. This level of patient empowerment increases confidence and ultimately minimise anxiety and depression. Despite the varying teaching and learning methods associated with individualised education, patient‐centred education has the potential to assist cardiac nurses in adequately preparing patients for discharge following their coronary artery bypass graft. Relevance to clinical practice: Development of individualised education programmes is crucial in preparing patients for discharge. The reduction in readmission to hospital has a significant effect on already stretched resources, and the reduction in postoperative complications during the recovery period linked with depression and anxiety will have a positive effect on the individuals' ability to self‐care, health and well‐being.